Treatment of Localized Gingival Recessions Using Gingival Unit Grafts: A Randomized Controlled Clinical Trial - YILDIRIM, HATİCE SELİN (WILEY, 2013)
Background: One of the success factors in periodontal plastic surgery is the synergistic relationship between involved tissues and vascular supply. Gingiva as a functional unit is unique with a specific vascular configuration and contains the supracrestal portion naturally created to survive over avascular root surfaces. The aim of this randomized controlled trial is to clinically evaluate the treatment of localized gingival recessions by using gingival unit grafts (palatal tissue involving marginal gingiva and papillae) compared with conventional palatal grafts. Methods: Seventeen patients with Class I to II recession defects on mandibular anterior teeth were included and randomly divided into two groups. Recessions were treated with gingival unit grafts in group 1 (n = 8) and with palatal grafts in group 2 (n = 9). Clinical parameters including vertical recession (VR), probing depth, keratinized tissue (KT), and attachment level were recorded at baseline and 8 months after surgery. Results: Both treatments produced significant clinical improvements within the groups. Intergroup comparison revealed significantly higher VR reduction, attachment, and KT gain in group 1 than in group 2; mean percentages of the defect coverage were 91.62% +/- 9.74% and 68.97% +/- 13.67%, respectively (P <0.05). Healing of the gingival unit donor site was uneventful. Conclusion: Within its limits, this study demonstrates the possibility of treating buccal recessions with gingival unit grafts as an alternative technique using gingival donor graft of site-specific vascular configuration, with better defect coverage, clinical, and esthetic improvements compared with palatal grafts. J Periodontol 2013;84:41-50.
Keywords: Autografting; gingiva; gingival recession; mouth mucosa; tooth root; transplants; DERMAL MATRIX GRAFT; CREEPING ATTACHMENT; CONNECTIVE-TISSUE; COVERAGE; SURGERY; FLAP; SMOKING